Detection of trace amount of arsenic in groundwater by laser-induced breakdown spectroscopy and adsorption - Haider, A F M Yusuf; Ullah, M. Hedayet; Khan, Zulfiqar H; Kabir, Firoza; Abedin, Kazi Monowar (© 2014 Optics and Laser Technology, 2017)
This article was published in the Journal Optics and Laser Technology [© 2013 Elsevier Ltd.] and the definite version is available at : 10.1016/j.optlastec.2013.09.002